Spiritual education of future teachers as a social phenomenon - Saidova Yulduz Zamon qizi (Periodica Journal, 2024)
This article comments on the content and essence of the concept of spirituality and the social significance of its formation in future specialists. Important factors for the formation and development of spirituality were explained, and its impact on the socio-economic sphere was explained by clear evidence. Spirituality is concerned with the connection of enlightenment, national pride, and selfawareness.
Keywords: Spirituality; enlightenment; education